2017
DOI: 10.1111/1467-8551.12240
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Labour−Management Partnership: A Longitudinal Case Analysis

Abstract: Issues of labour−management cooperation have long attracted the attention of management researchers, practitioners and policymakers. In Britain, the most recent wave of interest has been under the rubric of labour−management partnership, normally concerning the development of cooperative relations between unions and employers. A recurring theme is that cooperative relations can be difficult to develop and sustain, especially in liberal market economies. This paper advances the debate by examining the dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 61 publications
1
49
0
Order By: Relevance
“…The assumptions underpinning these two perspectives are different, although the boundary between them may be less easy to establish in practice. For example, in 'non-union partnerships' many of the roles of employee representatives, the issues discussed and the structures and processes of consultation can look similar to those in union partnerships (Johnstone et al 2010). Another example of porous borders in practice comes from Pyman et al (2006) who found that many unionized workplaces with well-established collective bargaining arrangements also had individualized, non-union forms of voice and participation.…”
Section: Applying the Co-operation Curvementioning
confidence: 99%
“…The assumptions underpinning these two perspectives are different, although the boundary between them may be less easy to establish in practice. For example, in 'non-union partnerships' many of the roles of employee representatives, the issues discussed and the structures and processes of consultation can look similar to those in union partnerships (Johnstone et al 2010). Another example of porous borders in practice comes from Pyman et al (2006) who found that many unionized workplaces with well-established collective bargaining arrangements also had individualized, non-union forms of voice and participation.…”
Section: Applying the Co-operation Curvementioning
confidence: 99%
“…In this setting, critical researchers condemn partnerships as a fool's game as neoliberal regimes of capital accumulation provide employers with no justification for honouring agreements with their unions (Dobbins and Dundon 2017;MacDonald 2014;Thompson 2003). However, even the 'mutual gains' literature, which stresses that cooperative labour relations can provide companies with an edge by improving efficiencies and product quality, increasingly recognizes that deepened cooperation is made arduous by the spread of low-cost HR models, a power imbalance in favour of employers and high paced technological change and deregulation (Guest and Peccei 2001;Johnstone and Wilkinson 2018;Kochan et al 2009;Valizade et al 2016).…”
Section: Explaining Variation In Partnership Outcomesmentioning
confidence: 99%
“…It could be argued that modern employers now recognise the value of 'good' people management, and employees now have alternative means of having a say, rendering trade unions superfluous or even unattractive (Grenier, 1988). Of course, critical and pluralist researchers of work and employment would reject such unitarist views given the 'structured antagonism' (Edwards, 1986) which means some conflicts of interest are inevitable and must be addressed (Johnstone, 2015;Johnstone & Wilkinson, 2017).…”
Section: Changing Trends In Work and Employmentmentioning
confidence: 99%